Glass carbomer and compomer for ART restorations: 3-year results of a randomized clinical trial - Oleg?rio da Costa, Isabel (My University, 2018)
Objective: To evaluate the survival of atraumatic restorative treatment (ART) restorations using high viscosity glass ionomer cement (GIC), compomer (COM), and glass carbomer (CAR) for occlusal and occlusoproximal cavitated dentin caries lesions in primary molars. Methods: A total of 568 4-7-year-old children (287 occlusoproximal and 281 occlusal cavities) were selected in Barueri, Brazil. The patients were randomly allocated in three groups: GIC, COM, and CAR. All treatments were performed on school setting following ART premises. Evaluations were performed after 2, 6, 12, 18, 24, and 36 months. Restoration survival was evaluated using Kaplan-Meier survival analysis and log-rank test, while Cox regression analysis was used for testing association with clinical factors (α = 5%). Results: The overall survival rate after 3 years of occlusal ART restorations was 73% (GIC = 83%; COM = 78%; CAR = 62%) and 49% for occlusoproximal ART restorations (GIC = 56%; COM = 56%; CAR = 36%). CAR restorations were less successful than GIC and COM for both occlusal and occlusoproximal restorations (p < 0.05). No difference was found between GIC and COM (p > 0.05). Conclusions: GIC and compomer are clinically more successful than CAR for occlusal and occlusoproximal restorations in primary molars. Clinical significance: Both compomer and high viscosity glass ionomer cement are suitable materials for ART in primary molars. However, glass carbomer cement should not be used for ART (#NCT02217098).
PUBLISHED
Keywords: A traumatic restorative treatment; Compomer; Glass carbomer; Glass ionomer cement; Primary teeth